2012
DOI: 10.1080/09593969.2011.634071
|View full text |Cite
|
Sign up to set email alerts
|

Supermarkets competition in England and planning regulation

Abstract: We adapt the Bresnahan and Reiss (1991. Entry and competition in concentrated markets. The Journal of Political Economy 99, no. 5: 977-1009) model to allow for multiple store formats. We estimate the model using data for English supermarkets, and evaluate the impact of restrictive planning regulation on entry into the English grocery retail industry. We find that more restrictive planning regulation reduces the number of large format supermarkets in equilibrium. However, the impact is overstated if variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Sadun (2011) finds that an increase in approved applications results in higher employment growth, and Haskel and Sadun (2011) find that retail TFP decreased following the 1996 planning regulation in U.K. Other studies using U.K. data are Griffith and Harmgart (2008); Haskel and Khawaja (2003) and Reynolds et al (2005). In France, regulation is found to slow labor growth (Bertrand and Kramarz, 2002).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sadun (2011) finds that an increase in approved applications results in higher employment growth, and Haskel and Sadun (2011) find that retail TFP decreased following the 1996 planning regulation in U.K. Other studies using U.K. data are Griffith and Harmgart (2008); Haskel and Khawaja (2003) and Reynolds et al (2005). In France, regulation is found to slow labor growth (Bertrand and Kramarz, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…The restrictions, however, differ substantially across countries. While some countries strictly regulate large entrants, more flexible zoning laws exist for instance in the U.S. (Hoj et al, 1995;Pilat, 1997;Boylaud and Nicoletti, 2001;Nicoletti and Scarpetta, 2003;Griffith and Harmgart, 2005;Pilat, 2005). In Sweden, the Plan and Building Act ("Plan och Bygglagen", PBL) empowers the 290 municipalities to make decisions on applications for new entrants.…”
Section: Entry Regulation and Datamentioning
confidence: 99%
“…Indeed, recent research has suggested that superstores located within, and on the edge of, town centres may have a positive effect on town centre resilience (Wrigley and Dolega, 2011;Wrigley et al, 2010; and that small shops in town centres and high streets have often themselves been resilient in the face of larger format corporate food store opening, contrary to fears emanating from the media and some pressure groups (Wrigley et al, 2009;Powe, 2012;Findlay and Sparks, 2012). However, analysis has suggested that the restrictive nature of retail land-use planning policies may have reduced retail productivity by as much as 20% (Cheshire et al, 2011; see also Griffith and Harmgart, 2012). In particular, retailers have found it challenging to construct larger, hypermarket stores (in excess of 60,000 sq ft) due to the "town centres first" thrust of retail planning policy:…”
Section: The Geography Of Recent Store Development Retail Saturationmentioning
confidence: 99%
“…As a result, Guy (2007, p. 149) contends that 'planners [in the UK] generally lack understanding of economic concepts in retailing, and that planning policies may inhibit innovation and productivity, at the same time distorting competition between retailers' (our emphasis). Indeed, Griffith and Harmgart (2008), in modelling the implications of retail planning regulation, found that customers paid higher prices as a result of the regulation which acted as a barrier to entry for retailers.…”
Section: Implications For Customer-facing Innovation and Sales Producmentioning
confidence: 99%
“…There have already been 'trade offs of efficiency against effectiveness' (Reynolds et al, 2005, p. 240) observed in the development of more flexible formats, but what this means in terms of retail productivity has only recently been explored (Griffith & Harmgart, 2008). By examining the various marketing management responses to regulatory tightening we can probe, not only the effect that changes in market rules have on industries and firms, but, more specifically, on the customer experience of retail brands.…”
Section: Introductionmentioning
confidence: 99%